When are Enhanced Relationship Tax Compliance Programs Mutually Beneficial? - De Simone, Lisa; Sansing, Richard C.; Seidman, Jeri K. (The Accounting Review, 2013)
ABSTRACT: This study investigates the circumstances under which “enhanced relationship” tax-compliance programs are mutually beneficial to taxpayers and tax authorities, as well as how these benefits are shared. We develop a model of taxpayer and tax authority behavior inside and outside of an enhanced relationship program. Our model suggests that, despite the adversarial nature of the relationship, an enhanced relationship program is mutually beneficial in many settings. The benefits are due to lower combined government audit and taxpayer compliance costs. These costs are lower because taxpayers are less likely to claim positions with weak support and the government is less likely to challenge positions with strong support inside the program. Further, we show that an increase in the ability of the tax authority to identify uncertain tax positions makes an enhanced relationship tax-compliance program more attractive to both the taxpayer and the tax authority. JEL Classifications: H26